Collateral damage from agricultural netting to open‐country bird populations in Thailand. Issue 11 (16th September 2022) - Angkaew, Rongrong; Round, Philip D.; Ngoprasert, Dusit; Powell, Larkin A.; Limparungpatthanakij, Wich'yanan; Gale, George A.
Abstract: Nets are used across a wide variety of food production landscapes to control avian pests typically resulting in deaths of entangled birds. However, the impact of nets on bird populations is a human–wildlife conflict that remains mostly unquantified. Here, we examined the scale of netting in the central plains of Thailand, a region dominated by ricefields, among which aquaculture ponds are increasingly interspersed. Nets/exclusion types, number of individual birds and species caught were recorded on 1312 road‐survey transects (2‐km length × 0.4‐km width). We also interviewed 104 local farmers. The transect sampling took place in late‐September 2020, and from December 2020 to April 2021. Each survey transect was visited only once. We found 1881 nets and barriers of parallel cords on 196 (15%) of the transects. Counts of nets and barriers were ~13 times higher than expected in aquaculture ponds based on their areal proportion, and vertical nets were the most commonly observed type ( n  = 1299). We documented 735 individuals of at least 45 bird species caught in the nets and parallel cords, including many species not regarded as pests. Approximately 20% of individuals caught in ricefields and 95% at aquaculture ponds were non‐target bycatch. Our interviews suggested that 55% of respondents thought nets were ineffective while only 6% thought they were effective. We suggest imposing a ban on netting, considering other mitigation strategies to reduce conflicts such as promoting the use of parallel cords, and prioritizing conservation actions with community participation. Further studies should investigate the efficacy of less deleterious deterrents. Abstract : Nets are used across a wide variety of food production landscapes to control avian pests typically resulting in the death of entangled birds. Based on 1312 road‐survey transects, we documented 735 individuals of at least 45 bird species caught in nets and parallel cords, including many species not regarded as pests. We suggest imposing a ban on netting.